Effective Repentance: Its Concept, Islamic Standpoint, And Way Of Its Application - Yusuf Olawale Owa-Onire Uthman (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2023)
Sincere repentance needs to earn full consideration, Islam recognizes repentance as a concept that serves a significant purpose in the life of the believers. Spiritually, it is very effective in Islam, especially when it’s connected with the intention of closeness to Almighty God. Therefore, this paper will rapidly showcase the position of perfect repentance through its meaning, condition, benefits, and the perspective of Islam on its notion. Our readers would realize with the result of this research that, oftentimes, the noble religion (Islam) has explained the course of real repentance, in order to enlighten mankind on its benefit. Meanwhile, with repentance, a man will stay closer to God, know the right relationship with a fellow human, and run away from sins and evil. However, the master of repentance (seyyid ul-istigfar) would be addressed to fulfil the real meaning of this special prayer and correct the people’s fallacies connected to it. While in the study, repentance in a meaningful way will be detailed regarding verses of the Qur’an, prophetic tradition, and scholars’ work to derive quality research for this paperwork.